An investigation of the phase behaviors for quaternary U-Nb/Mo-Ti-Zr metallic fuel alloys. (March 2022) - Zhuo, Weiqian; Wu, Huali; Benson, Michael T.; Zhang, Jinsuo
Abstract: Quaternary fuel alloys containing U, Nb/Mo, Ti, and Zr are proposed as fuel candidates for sodium-cooled fast reactors (SFRs). In this work, two Nb-bearing alloys, i.e., U-NT5Z (U‐2.5Nb‐2.5Ti‐5.0Zr in wt%) and U-NT7Z (U‐1.5Nb‐1.5Ti‐7.0Zr in wt%), and two Mo-bearing alloys, i.e., U-MT5Z (U-2.5Mo-2.5Ti-5.0Zr in wt%) and U-MT7Z (U-1.5Mo-1.5Ti-7.0Zr in wt%) were characterized and compared. The characterization techniques were differential scanning calorimetry (DSC), X-ray powder diffraction (XRD), and scanning electron microscopy/energy dispersive X-ray spectroscopy (SEM/EDS). DSC was performed to obtain the transition behaviors, and XRD and SEM/EDS were applied for phase identification. The results were combined to obtain the solid-state phase transitions between 500 °C and 850 °C for the alloys. It is found that the Nb-bearing alloys comprise similar phase transition behaviors as the Mo-bearing alloys. The phase transitions in U-NT5Z are α → γ at 608 °C and U2 Ti → γ at 627 °C, which are ~40 °C higher than that of U-MT5Z. The phase transition in U-NT7Z is α → γ at 645 °C, and is 23 °C higher than that of U-MT7Z. Highlights: Quaternary fuel alloys containing U, Nb/Mo, Ti, and Zr are proposed as fuel candidates for sodium-cooled fast reactors. Two Nb-bearing alloys and two Mo-bearing alloys were characterized. Nb-bearing alloys comprise similar phase transition behavior as Mo-bearing alloys. The γ phase onset temperatures of Nb-bearing alloys are higher than the Mo-bearing alloys.